Analisis Kesalahan Berbahasa pada Cerpen yang Berjudul Badai yang Reda dan Hutan Merah Karya Fauzia sebagai Kelayakan Bahan Ajar Membaca Intensif Mahasiswa Pendidikan Bahasa dan Sastra Indonesia Universitas Negeri Semarang - Tri Maria Hastuti; Amanda Ayu Ningrum; Tyas Rahma Viani; Seruni Yunita Chairunnisa; Muhamad Syafiq Asyam; Asep Purwo Yudi Utomo; Rujiani Rujiani (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2024)
Language use in everyday life is often incorrect, particularly in informal conversations. The correct and proper use of language also impacts an individual's reading process. Quality writing is characterized by the use of good and correct language conventions. However, many still encounter language errors in texts. Analyzing syntactic errors in short stories is necessary to identify and explain them. The aim of this study was to analyze language errors in the short stories "The Ceded Storm" and "The Red Forest" by Fauzia, as part of an intensive reading program for Indonesian language and literature students at Semarang State University. The study employed deductive methods and theoretical approaches, conducting analyses by identifying language errors in the short stories. A qualitative descriptive approach was used as part of the methodology, while language error analysis incorporated a theoretical framework. Data collection techniques included reading and note-taking. The data collection process involved three steps: (1) data collection, (2) data analysis, and (3) data presentation. Researchers examined the short stories "The Ceded Storm" and "The Red Forest" by Fauzia. The research highlighted numerous potential errors, including capitalization, punctuation, word choice or diction, usage of strong words, and conjunctions. The study aimed to identify factors contributing to the short stories' lack of quality and provide insights through a detailed analysis.